WE SUPPORT YOU: ACADEMIC PERFORMANCE AND SPORTS INVOLVEMENT AMONG UNIVERSITY STUDENTATHLETES - Patricia Pawa Pitil,; Siti Maisarah Binti Azharin, (Journal of Islamic, Social, Economics and Development, 2021)
One of the misconceptions about the university student-athletes is that they may notbe capable to strive in academic performance towards academic excellence. This has becomea stigma to those who are actively involved in sports. Correspondingly, the challenge ofbalancing academic standards with athletic competitiveness is not new. Therefore, this studyaimed to assess the student-athletes from UiTM Sarawak (N=168) on the factors of thesurrounding environment (support system) affecting sports involvement, and the perceivedhealth condition in relation to academic performance (GPA). The data were gathered using thesurvey method where the questionnaire was distributed through an online platform. The resultsindicated that there was no significant relationship between GPA and the perceived healthcondition, and the support system (p > .05). For gender comparison, there was a significantdifference in the perceived health condition (p <.05), but not in the support system (p > .05).Conclusively, the student-athletes has a good health condition level, with females beingperceived to be at a higher level, and have great support from the environment in their sportscareer; where the academic achievements are concerned, regardless of the gender, the studentathletesare in good hands. It is recommended that the supports that are given to these studentathletesbe maintained and to promote sports participation to the non-athletes.